Reciprocally Retained Genes in the Angiosperm Lineage Show the Hallmarks of Dosage Balance Sensitivity - Tasdighian, Setareh; Van Bel, Michiel; Li, Zhen; Van de Peer, Yves; Carretero-Paulet, Lorenzo; Maere, Steven (The Plant cell, 2017)
In several organisms, particular functional categories of genes, such as regulatory and complex-forming genes, are preferentially retained after whole-genome multiplications but rarely duplicate through small-scale duplication, a pattern referred to as reciprocal retention. This peculiar duplication behavior is hypothesized to stem from constraints on the dosage balance between the genes concerned and their interaction context. However, the evidence for a relationship between reciprocal retention and dosage balance sensitivity remains fragmentary. Here, we identified which gene families are most strongly reciprocally retained in the angiosperm lineage and studied their functional and evolutionary characteristics. Reciprocally retained gene families exhibit stronger sequence divergence constraints and lower rates of functional and expression divergence than other gene families, suggesting that dosage balance sensitivity is a general characteristic of reciprocally retained genes. Gene families functioning in regulatory and signaling processes are much more strongly represented at the top of the reciprocal retention ranking than those functioning in multiprotein complexes, suggesting that regulatory imbalances may lead to stronger fitness effects than classical stoichiometric protein complex imbalances. Finally, reciprocally retained duplicates are often subject to dosage balance constraints for prolonged evolutionary times, which may have repercussions for the ease with which genome multiplications can engender evolutionary innovation.